18F-FDG Pet-Guided External Beam Radiotherapy in Iodine-Refractory Differentiated Thyroid Cancer: A Pilot Study. (19th October 2017) - Farina, Eleonora; Monari, Fabio; Castellucci, Paolo; Romani, Fabrizio; Repaci, Andrea; Farina, Arianna; Rambaldi, Giuseppe Zanirato; Frezza, Giovanni; Mazzarotto, Renzo; Cammelli, Silvia; Tagliaferri, Luca; Autorino, Rosa; et al.
Abstract : Introduction . To evaluate the clinical response rate after a postoperative 18 F-FDG PET/CT guided external beam radiotherapy (EBRT) in Iodine-refractory differentiated thyroid cancer. Material and Methods . Patients with thyroid cancer locally recurrent after total thyroidectomy plus metabolic radiotherapy and treated with radical EBRT were included. Inclusion criteria were detectable thyroglobulin (Tg), negative postmetabolic radiotherapy whole body scintigraphy, and no surgical indications. The pretreatment 18 F-FDG PET/CT resulted positive in all cases (loggia, lymph nodes, and lung). EBRT was delivered with IMRT-SIB technique. A 18 F-FDG PET/CT revaluation and Tg dosage were performed 3 months after the treatment. Results . Sixteen consecutive patients were included in this analysis (median follow-up: 6–44 months). Post-EBRT 18 F-FDG PET/CT showed CR in 43.7%, PR in 31.2%, SD in 25.0% patients, and PD due to lung metastases in 12.5%. Overall response rate was 75.0% (CI 95%: 41.4–93.3%). Tg levels decreased in 75.0% with a median Δ of 68.0%. Two-year PFS and OS rates were 80.0% and 93.0%, respectively. Acute G3 toxicity occurred in 18.7% and late G2 toxicity in 12.5%. Conclusions.    18 F-FDG PET/CT was useful in target definition for radiotherapy planning, identifying positive areas not detected with 131 I scintigraphy. IMRT based EBRT was feasible and our results encourage future prospective studies. This clinical trial is registered with ID:NCT03191643 .